Sequelae of delayed replantation of maxillary permanent incisors after avulsion: A case series with 24-month follow-up and clinical review - Shaik Hasanuddin; J Sharada Reddy (Wolters Kluwer Medknow Publications, 2018)
Replantation of avulsed incisors in young children is a successful treatment modality. Almost all replanted teeth exhibit ankylosis followed by inflammatory or replacement resorption, as immediate replantation is practically rare. The purpose of the review is to report a series of cases of prolonged delay in replantation of avulsed incisors and discuss its sequelae, leading to different patterns of root resorption after a minimum follow-up period of 24 months. The present case series is a follow-up of five cases of delayed replantation (more than 24 h delay) without any root surface treatment. Extraoral endodontic therapy was performed before replantation. The avulsed teeth were stabilized using an acid-etch composite resin splint for 4 weeks. The patients were followed up at 3, 6, and 12 months interval and half-yearly thereafter, for examination of the replanted teeth clinically and radiographically. After 24-month follow-up, the replanted teeth were evaluated for gingival changes and clinical mobility. The radiographs were evaluated for external root resorption or inflammatory resorption, osseous root replacement, or replacement resorption. The case series concludes that avulsed teeth transported in dry as well as dessicated conditions and replanted after a delay of 24 h have a survival rate of more than 24 months, though there is no promising long-term prognosis. The sequelae in most of the cases are surface resorption followed by inflammatory resorption or resorption due to pulpal infection or replacement resorption.